Lactococcus G423 improve growth performance and lipid metabolism of broilers through modulating the gut microbiota and metabolites - Wang, Mi; Ma, Wei; Wang, Chunqiang; Li, Desheng (Frontiers in Microbiology, 2024)
This study aimed to explore whether Lactococcus G423 could improve growth performance and lipid metabolism of broilers by modulation of gut microbiota and metabolites. A total of 640 oneday-old AA broilers were randomly divided into 4 groups (Control (CON), Lac_L, Lac_H, and ABX). Average daily gain (ADG), average daily feed intake (ADFI), feed conversion ratio (FCR), breast muscle, thigh muscle and abdominal fat pad were removed and weighed at 42 d of age.Serum was obtained by centrifuging blood sample from jugular vein (10 ml) for determining highdensity lipoprotein (HDL), total cholesterol (TC), low-density lipoprotein (LDL) and triglyceride (TG) using ELISA. The ileal contents were harvested and immediately frozen in liquid nitrogen for 16S rRNA and LC-MS analyses. Then, the results of 16S rRNA analysis were confirmed by quantitative polymerase chain reaction (qPCR). Compared with the CON group, FCR significantly decreased in the Lac_H group (P<0.05) in 1-21d; ADG significantly increased and FCR significantly decreased in the Lac_H group (P<0.05) in 22-42d. 42d weight body and ADG significantly increased in the Lac_H group (P<0.05) in 42d. Abdominal fat percentage was significantly decreased by Lactococcus G423 (P<0.05), the high dose of Lactococcus G423 significantly decreased the serum of TG, TC and LDL level (P<0.05), the low dose of Lactococcus G423 significantly decreased the serum of TG and TC level (P<0.05) . A significant difference in microbial diversity was found among the four groups. Compared with the CON group, the abundance rates of Firmicutes and Lactobacillus in the Lac_H group were significantly increase (P<0.05). The global and overview maps and membrane transport in the Lac_L, Lac_H, and ABX groups significantly changed versus those in the CON group (P<0.05). The results of LC-MS demonstrated that Lactococcus could significantly improve the levels of some metabolites (6-hydroxy-5-methoxyindole glucuronide, 9,10-DiHOME, N-Acetyl-L-phenylalanine, and kynurenine), and these metabolites were involved in 4 metabolic pathways. Among them, the pathways of linoleic acid metabolism, phenylalanine metabolism, and pentose and glucuronate interconversions significantly changed (P<0.05). Lactococcus G423 could ameliorate growth performance and lipid metabolism of broilers by modulation of gut microbiota and metabolites.